Does good food make male mice sexy? The influence of diet on male sexually selected traits - Porwal, Neelam; Gangothri, S.; Agarwal, Himrekha; Guenther, Anja (Frontiers in Ecology and Evolution, 2023)
Diet may have an important influence on life history and behavioral traits involved in sexual selection. Males of high condition should be better able to bear the costs of high trait expression and hence express more elaborate sexual signals. Here, we follow Mus musculus domesticus raised in seminatural conditions across four generations of standard (SQ) versus high quality (HQ) food, containing a higher energy level and manufactured to boost body condition during reproduction. We investigate multivariate effects on life history, pre-and post-copulatory traits of males. In addition, we investigate the effects of a food switch in the third generation on trait expression. From the F3 generation on, HQ males were more dominant. This resulted in HQ males being preferred in mate choice even though no post-copulatory traits were affected, suggesting a condition-dependent allocation to different traits. Sons of food switched males showed reduced pre-but not post-copulatory trait expression, irrespective of the direction of the food switch, indicating a mismatch rather than adaptive plastic adjustments in the first generation. We conclude that males balance investment into different traits based on the diet to achieve similar fitness. Furthermore, we show that adaptive shifts in male reproductive strategies need several generations to emerge while first responses to changing environments reflect a constrained trait expression.